2016
DOI: 10.1617/s11527-016-0826-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental bond behaviour of GFRP and masonry bricks under impulsive loading

Abstract: Fibre Reinforced Polymers have become a popular material for strengthening of masonry structures. The performance of this technique is strongly dependent on the bond between the FRP and the substrate. Understanding the strain rate effect on these materials and strengthening techniques is important for proper design and proper modelling of these systems under impacts or blast loads. This work aims to study the behaviour of the bond between GFRP and brick at different strain rates. A Drop Weight Impact Machine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The dynamic FRP stiffness and dynamic brick strength at a given slip rate can be calculated by combining Equations ( 9), ( 10) and (13). Then, the bond-slip parameter at a given slip rate can be calculated by substituting the dynamic FRP stiffness and dynamic brick strength into the empirical formulas (11) and (12). The maximum bond stress and the corresponding slip calculated by the empirical formulas were compared with the test and numerical results.…”
Section: Empirical Formulas and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic FRP stiffness and dynamic brick strength at a given slip rate can be calculated by combining Equations ( 9), ( 10) and (13). Then, the bond-slip parameter at a given slip rate can be calculated by substituting the dynamic FRP stiffness and dynamic brick strength into the empirical formulas (11) and (12). The maximum bond stress and the corresponding slip calculated by the empirical formulas were compared with the test and numerical results.…”
Section: Empirical Formulas and Validationmentioning
confidence: 99%
“…The masonry structure is likely to be subjected to dynamic loads such as earthquakes, explosions and impacts. Experimental studies of the FRP-to-substrate interface show that the dynamic interfacial strength is significantly higher than that of static [ 10 , 11 , 12 , 13 ], and the dynamic bond–slip relationship is naturally different from that of static [ 14 , 15 , 16 , 17 , 18 ]. An accurate bond–slip relationship can be used for strength calculations of FRP-reinforced structures, helping to design safer and more economical FRP-reinforced solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentation is, in the field of fast dynamics, still at a higher level with respect to numerical modeling (Buchan and Chen 2007). Some laboratory tests have been performed to evaluate the response of the masonry under such extreme loads, see for (Pereira and Lourenço 2016b;Pereira et al 2015;Pereira and Lourenço 2016a;Hao and Tarasov 2008;Dennis et al 2002;Baylot et al 2005). In converse, few numerical studies on the response of masonry under blast or impact actions are found in the literature; one may recall the contributions by (Wu et al 2005;Zapata and Weggel 2008;Macorini and Izzuddin 2014;Burnett et al 2007).…”
Section: Strain-rate Dependency Of the Modeling Strategiesmentioning
confidence: 99%
“…Through an extensive literature review, an experimental database of 1583 individual shear pull-tests on masonry specimens was compiled from across 56 published studies [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] .…”
Section: Datamentioning
confidence: 99%
“…The data therefore excludes the following: Specimens subjected to effects such as temperature and moisture [5] , [25] , [29] , [33] , [41] , [46] , [51] , [52] ; Tests in which additional anchorage between the FRP and substrate was provided. For example those with nails, fans or cogs [9] , [18] , [24] , [30] , [32] , [55] ; Tests in which the FRP was bonded to plaster instead of directly to the masonry substrate [9] , [39] , [42] , [55] , [56] ; Non-quasi-static loading conditions such as impulse loads [54] ; and Plates manufactured from textile-reinforced mortars or fibre-reinforced cementitious mortars. …”
Section: Datamentioning
confidence: 99%